2013
DOI: 10.1038/modpathol.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass staining in renal biopsies with membranous glomerulonephritis indicates subclass switch during disease progression

Abstract: Recent breakthrough findings revealed that most patients with idiopathic (primary) membranous glomerulonephritis have IgG4 antibodies to the phospholipase A2 receptor (PLA2R). These IgG4 antibodies can be detected in the glomerular immune complexes and they colocalize with PLA2R. In secondary forms of membranous glomerulonephritis, such IgG4 antibodies are absent or less prevalent. There are no studies addressing the IgG subclass distribution across different stages of membranous glomerulonephritis. During a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 23 publications
4
104
2
3
Order By: Relevance
“…Some scholars showed that, mainly IgG antibody, especially IgG4 was the dominant IgG subclass in primary membranous glomerulonephritis, however, in secondary membranous glomerulonephritis IgG1 is dominant [18]. It is also known that the generation of a high-affinity long-lived antibody response requires the presence of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 98%
“…Some scholars showed that, mainly IgG antibody, especially IgG4 was the dominant IgG subclass in primary membranous glomerulonephritis, however, in secondary membranous glomerulonephritis IgG1 is dominant [18]. It is also known that the generation of a high-affinity long-lived antibody response requires the presence of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 98%
“…We chose to screen patients for the IgG4 anti-PLA2R1 subclass because many studies have shown that IgG4 is the predominant IgG subclass in iMN, correlating the most with disease activity. 8,20,21 Successive deletion of CysR, CTLD1, and CTLD7 led to the progressive loss of PLA2R1 recognition for 12, then 11 and 27 more patients, identifying three epitope profiles that likely correspond to three distinct epitopes in each of these domains ( Figure 1, C-E).…”
Section: Identification Of Three Epitope Profilesmentioning
confidence: 99%
“…8,20,21 To confirm this view, we compared the reactivity of sera from patients selected from the three epitope groups by Western blot on the deletion mutants of PLA2R1 (Figure 1) and by ELISA on CysR, CTLD1 and CTLD7 antigens with detection for the different IgG subclasses (1, 2, 3 and 4) and total IgGs (Supplemental Figure 8). To ascertain our results, we validated the specificity of IgG subclass detection with purified IgGs (Supplemental Figure 8A) and then performed Western blot assays and ELISAs with simultaneous detection for all IgGs (Supplemental Figure 8, B-F).…”
Section: Igg Subclassesmentioning
confidence: 99%
“…One is based on an observation that the earliest deposits in primary MN have both IgG1 and C1q (74), as well as the fact that there are usually low but detectable levels of the complement-fixing IgG1 and/or IgG3 subclasses of anti-PLA 2 R present in the circulation (24). Thus, complement could be activated and sustained at a low level by the classical pathway, even though IgG4 is predominant and may have other immunomodulatory or pathophysiological functions.…”
Section: Differences Between Pla 2 R-associated Mn and The Paradigm Ementioning
confidence: 99%